Analysis of Hospital Patient Satisfaction in Indonesia: Systematic Review - Rahayu, Eka Putri; Ariyanti, Rea (Panakeia Journal of Epidemiology, 2024)
Patient satisfaction has been remarkably low in most developing countries leading to competition between private and public health institutions. The satisfaction of clients is one essential factor to success of every organization. It is the aim of the review to analyze hospital patient satisfaction in Indonesia. This study used the PRISMA (Preferred Reporting Items for Systematic Review and Meta Analysis) method. A comprehensive literature review was conducted using the following databases: Science Direct, Pub Med, Google Scholar. The period was 2020-2024. It shows that obtained 103 articles with the keyword “hospital” “patient” “satisfaction” “Indonesia”. The articles were filtered based on the suitable of the title, abstract, content, and selected those that met the criteria, so that there were 100 articles that were assessed for suitability. So, there are 6 articles that can be analyzed and discuss about hospital patient satisfaction in Indonesia. Patients generally express satisfaction with service quality, particularly both in private and public hospitals. However, there is room for improvement in public hospitals, especially in terms of responsiveness, attentiveness, and reliability of medical staff.